Interferon signaling suppresses the unfolded protein response and induces cell death in hepatocytes accumulating hepatitis B surface antigen - Baudi, Ian; Isogawa, Masanori; Moalli, Federica; Onishi, Masaya; Kawashima, Keigo; Ishida, Yuji; Tateno, Chise; Sato, Yusuke; Harashima, Hideyoshi; Ito, Hiroyasu; Ishikawa, Tetsuya; Wakita, Takaji; et al. (PLoS pathogens, 2021)
Virus infection, such as hepatitis B virus (HBV), occasionally causes endoplasmic reticulum (ER) stress. The unfolded protein response (UPR) is counteractive machinery to ER stress, and the failure of UPR to cope with ER stress results in cell death. Mechanisms that regulate the balance between ER stress and UPR are poorly understood. Type 1 and type 2 interferons have been implicated in hepatic flares during chronic HBV infection. Here, we examined the interplay between ER stress, UPR, and IFNs using transgenic mice that express hepatitis B surface antigen (HBsAg) (HBs-Tg mice) and humanized-liver chimeric mice infected with HBV. IFNα causes severe and moderate liver injury in HBs-Tg mice and HBV infected chimeric mice, respectively. The degree of liver injury is directly correlated with HBsAg levels in the liver, and reduction of HBsAg in the transgenic mice alleviates IFNα mediated liver injury. Analyses of total gene expression and UPR biomarkers’ protein expression in the liver revealed that UPR is induced in HBs-Tg mice and HBV infected chimeric mice, indicating that HBsAg accumulation causes ER stress. Notably, IFNα administration transiently suppressed UPR biomarkers before liver injury without affecting intrahepatic HBsAg levels. Furthermore, UPR upregulation by glucose-regulated protein 78 (GRP78) suppression or low dose tunicamycin alleviated IFNα mediated liver injury. These results suggest that IFNα induces ER stress-associated cell death by reducing UPR. IFNγ uses the same mechanism to exert cytotoxicity to HBsAg accumulating hepatocytes. Collectively, our data reveal a previously unknown mechanism of IFN-mediated cell death. This study also identifies UPR as a potential target for regulating ER stress-associated cell death.